2016 IEEE 13th International Conference on Wearable and Implantable Body Sensor Networks (BSN) 2016
DOI: 10.1109/bsn.2016.7516255
|View full text |Cite
|
Sign up to set email alerts
|

Blind source separation and artefact cancellation for single channel bioelectrical signal

Abstract: Abstract-Bioelectrical signal analysis is gaining significant interests from both academics and industries due to its capability for improved diagnosis and therapy of chronic diseases. In practice, different bio-signals, such as EEG, ECG, EOG and EMG, are usually contaminating each other, and the measured signal is the linear combination of them. It is critical to separate them since analysis of one type or several of them separately is of more interest. In the case of multichannel recording, several blind sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The main idea of artefact identification is to determine what frequencies dominate in the recorded signal. If the signal frequencies deviate significantly from the frequency of the EEG signal, the classifier selects this fragment as the artefact [6,12,13].…”
Section: Methods Of Artefact Correctionmentioning
confidence: 99%
See 3 more Smart Citations
“…The main idea of artefact identification is to determine what frequencies dominate in the recorded signal. If the signal frequencies deviate significantly from the frequency of the EEG signal, the classifier selects this fragment as the artefact [6,12,13].…”
Section: Methods Of Artefact Correctionmentioning
confidence: 99%
“…The most popular methods of removing artefacts are PCA and ICA [6,16]. This paper contains a comparison between removing artefacts from the signal gathered from a stationary and a mobile amplifier.…”
Section: Methods Of Artefact Correctionmentioning
confidence: 99%
See 2 more Smart Citations
“…SSA has been used to analyse EEG recordings in several studies. For instance, Maddirala et al proposed to utilize SSA-based method to remove EOG, EMG, [25]- [27] and motion artifacts [28] from single-channel EEG; Zhang et al demonstrated the feasibility of ECG artifacts removal from single-channel EEG by the combination of SSA and BSS method [29]; Hu et al proposed to employ SSA-based method for extracting brain rhythms from EEG recordings [30]. Based on previous studies, we know that SSA has been successfully utilized for various artifacts removal from EEG, even has enabled the separation of different sources overlapping in time-frequency space.…”
Section: Introductionmentioning
confidence: 99%